Corpo e conhecimento no Timeu e no Brhadãranyaka- Upanisad: um estudo crítico baseado na teoria da enunciação metafórica e do símbolo mítico - Medeiros, Gracilene Felix (2017)
This thesis primarily aims to identify the metaphorical and symbolic representation of the body as an instrument to achieve contemplative knowledge noûs (Greek) and jñāna (Sanskrit), in the following corpus: Timaeus and Bṛhadāraṇyaka-Upaniṣad. It is suggested that the interpretation of the metaphorical utterance construction, as well of the symbolic statement of the body and knowledge, is a means for developing the literary analysis of Timaeus and Bṛhadāraṇyaka-Upaniṣad. It can be noted that among the range of possibilities of body reading and within the knowledge about the texts that shape our corpus, such as philosophical reading, historical, of the science of religions, metaphorical and symbolic interpretation is left on the sidelines. Nonetheless, metaphorical enunciation and symbolic statement interpretation enable the understanding and the resignification of the former literature. That is possible, due to the new meaning presented by those texts, which are structured in the field of language. The adopted methodology is based on a hermeneutical analysis of Timaeus and Bṛhadāraṇyaka-Upaniṣad. The Platonic dialogue and the quoted Indian text are critically inspected and interpreted in the light of a bibliographical method, based on Paul Ricoeur's (2005), (2009), (2014) metaphor and symbol theory. The counterpoint is presented by Eliade (2010a), (2010b), (2010c), (2010d) and Cassirer (2001), (2005). This research regards the body and the knowledge as analysis categories of the texts that build our analytical corpus. The raised issue is to what extent the body, as a vehicle to interpret a metaphorical enunciation or a symbolic statement, becomes a means to achieve the knowledge presented by Timaeus and Bṛhadāraṇyaka-Upaniṣad, which acknowledge the metaphorical and symbolic exegetic. It is assumed that the interpretation of contemplative knowledge, through the metaphorical and symbolic body, occurs solely on the work field. Outside the text framework, the designed interpretation does not present the same understanding of living metaphor or mythical symbol. In order to reach this comprehension, the present study has been limited to a certain time and space. Therefore, this research begins with the symbolic and mythic representation of the body, depicted in the epic and the Vedic verses. The initial approach establishes a comparison between the greek and the archaic indian texts, considering that the indo-european possible existence allows a proximity of the poems and hymns produced by these civilizations. Having established the basal literature, it was defined its respective portrayed bodies. Thereupon, this study aims to percept the body as a mythical and ritualistic element, pictured in these works as a dead body. This understanding is essential to the recognition of the body as a living element, conceived in the texts that compose the working corpus. Thus, it can be concluded that the body, as a dead symbol presented in the funeral rites and in the epic and Vedic texts, determines the existence of the living body. The latest is acknowledged in texts related to corpus analysis and, throughout metaphorical and symbolic interpretation, the living body reaches knowledge and establishes the balance of the human being.